Implementasi Aplikasi E-Masjid dalam Penguatan Administrasi dan Transparansi Keuangan - Effendi, Yusli; Triarda, Reza; Fahadayna, Adhi Cahya (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The digitalization of mosque administration has become essential for improving transparency, efficiency, and accountability in institutional governance. This study aims to analyze the effectiveness of training on the use of the E-Masjid application in enhancing the competencies and readiness of mosque administrators to adopt technology-based administrative systems. The study employed a participatory, practice-oriented training model consisting of conceptual briefings, demonstrations, and simulations, involving 26 participants from six mosques representing diverse institutional categories. The results indicate substantial improvements in participants’ understanding of mosque digitalization concepts, technical abilities in operating the application, and readiness for implementation, with an average score increase of 60–80%. The digitalization of financial management, congregational data, and asset inventories significantly strengthened accountability, improved congregational trust, and facilitated structured management of social programs. The findings reveal that successful integration of digital systems requires adequate infrastructure and improved digital literacy among mosque administrators. This study contributes to the growing body of literature on community-based digital governance and offers a replicable model for digital transformation in various mosque settings. The implications highlight the importance of sustained mentoring to ensure that digitalization becomes an integral component of modern, responsive mosque governance.